2003
DOI: 10.1590/s0100-879x2003000900018
|View full text |Cite
|
Sign up to set email alerts
|

Do endogenous opioids and nitric oxide participate in the anticonvulsant action of dipyrone?

Abstract: It was previously reported that systemic administration of dipyrone inhibited the tonic component of generalized tonic-clonic seizures in both the electroshock and the audiogenic seizure models. The aim of the present study was to investigate the mechanisms involved in the anticonvulsant action of dipyrone by assessing the role of nitric oxide and opioids in the electroshock (female 60-to 90-day-old Wistar rats, N = 5-11) and audiogenic seizure (female 60-to 90-day-old Wistar audiogenic rats, N = 5-11) models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…The most frequent behavioral sequences produce the following SI values: 0.11 = wild running with only one running fit; 0.23 = wild running with only one running fit, jumping and atonic falling; 0.38 = wild running with two running fits, jumping and atonic falling; 0.61 = all of the above plus tonic convulsion (back arching tonus); 0.73 = all the above plus partial (only forelimb or hindlimb) and generalized (forelimb and hindlimb) clonic seizures; 0.85 = all the above plus clonic spasms; 0.90 = all the above plus ventral flexion of the head; 0.95 = all the above plus forelimb hyperextension; 1.0 = all the above plus forelimb and hindlimb hyperextension. 17 In the present study only animals with SI > 0.85 (running, jumping plus clonic spasms) were included in the experimental groups.…”
Section: Acoustic Stimulation and Behavioral Evaluation Of Seizure Sementioning
confidence: 99%
“…The most frequent behavioral sequences produce the following SI values: 0.11 = wild running with only one running fit; 0.23 = wild running with only one running fit, jumping and atonic falling; 0.38 = wild running with two running fits, jumping and atonic falling; 0.61 = all of the above plus tonic convulsion (back arching tonus); 0.73 = all the above plus partial (only forelimb or hindlimb) and generalized (forelimb and hindlimb) clonic seizures; 0.85 = all the above plus clonic spasms; 0.90 = all the above plus ventral flexion of the head; 0.95 = all the above plus forelimb hyperextension; 1.0 = all the above plus forelimb and hindlimb hyperextension. 17 In the present study only animals with SI > 0.85 (running, jumping plus clonic spasms) were included in the experimental groups.…”
Section: Acoustic Stimulation and Behavioral Evaluation Of Seizure Sementioning
confidence: 99%
“…it has been shown that metamizole reduces the common bile duct and oddi sphincter tonus in a dose-dependent manner as well as the efferent urinary tract and urinary vesicle motility. in the last 10 years the interest in this compound has increased due to additional reported benefits, like antiapoptotic, neuroprotective, and anticonvulsant effects (68,80,82,102). there are animal studies which support the combined treatment with nSAiDs such as metamizole, with therapeutic hypothermia in order to render long-lasting neuroprotection.…”
Section: Other Effectsmentioning
confidence: 99%
“…A resting period of at least one week after screening was allowed before the initiation of the experimental protocols. The most frequent behavioral sequences produce the following SI values: 0.11 = wild running with only one running fit; 0.23 = wild running with only one running fit, jumping and atonic falling; 0.38 = wild running with two running fits, jumping and atonic falling; 0.61 = all of the above plus tonic convulsion (back arching tonus); 0.73 = all of the above plus partial (only forelimb or hindlimb) and generalized (forelimb and hindlimb) clonic seizures; 0.85 = all the above plus clonic spasms; 0.90 = all of the above plus ventral flexion of the head; 0.95 = all of the above plus forelimb hyperextension; 1.0 = all of the above plus forelimb and hindlimb hyperextension (14). Animals with SI >0.85 were included in the experiments.…”
Section: Methodsmentioning
confidence: 99%